Construyendo nuestra identidad nacional La trampa del ingreso medio y la procrastinación de las reformas - Barrera Herrera, Jorge (2013)
In this paper, we analyze what would be the main limiting our national institution. Initially described the global and national economic situation as a prelude to understanding the current global economic and social context in which we are immersed and outlook to face, highlighting the possible initiation of a global downward economic cycle the term of monetary policies conventional low interest rates close to zero, in the advanced countries. It is estimated that Peru will continue to be the country with higher growth and lower inflation in the region, no debt and high international reserves, enabling us to adequately address any overall negative external economic contingency. With regard to the factors limiting our national institutional development, are reviewed every one of them, identified as most important: finish building our national identity, improve educational quality, the worrying status quo bias, complacency by the trap average income and the game and political calculation. The National Institutions, now more than ever, is compromised by the increasingly evident interconnections of global policies and spillovers, demanding new and better coordinated actions among countries not yet reached. One concludes that the values, the affirmation of national identity, improving the quality of education, the most important limiting factors to overcome, allowing us to reach critical mass population with the required institutional level, which will achieve a efficient management of public resources, implementing sustained public policies for the benefit of the majority in a friendly relationship with nature.